The sensible guide to Forex : safer, smarter ways to survive and prosper from the start - Wachtel, Cliff, 1959- (Hoboken, New Jersey : Wiley, 2012)
"The traders' guide to making the most of one the hottest areas in finance: Forex tradingStart Trading Forex Right Now is the accessible introduction to one of today's most convenient way to make money written by a trader for traders. Forex offers some of the best reward/risk opportunities of any financial markets, and this book is designed to fit the way traders actually think and execute. Walking the reader through selecting a trading plan based on evidence that supports the plan (complete with benchmarks for selecting evidence), the book also provides simple technical analysis tools, along with concrete examples and anecdotes, that show how and when to buy low and sell high, along with step-by-step information on how to enter and exit a trade and understand leverage and risk. Throughout, the book stresses one key theme: plan and execute high probability trades or, at the very least, avoid big losses. Exploring how to avoid "mindless trading," the book covers everything you need to know, authored by Seeking Alpha's number one currency strategy opinion leader, Cliff Wachtel. The professional's guide to Forex trading, one of the easiest ways to trade Packed with visual data to bring the topic to life Includes appendices full of additional online resources including trading platforms and discussion forums Designed specially for individual and retail traders The practical, accessible introduction to Forex trading, Start Trading Forex Right Now is essential reading for any trader interested in getting started in currency trading"--
How Margin, Lot Size, and Leverage InteractThe Importance of Adequate Capital; Margin Calls: Your account's Circuit Breaker; Order Types; Exit Orders: Ways to Close a Position; The Three Facets of Risk and Risk Control; Example; The Core Four: The Most Important Skills for Success; Trader Psychology; Risk and Money Management (RAMM); Technical and Fundamental Analysis; CHAPTER 3 Technical Analysis (TA) Basics; Candle Chart Basics; Candle Anatomy and Meaning; Relationship between Body, Wick, and Its Significance; Support and Resistance (S/R) Basics; Candle Chart Time Frames: Length Matters.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Foreign exchange market; Foreign exchange futures; Foreign exchange market; Foreign exchange futures; BUSINESS & ECONOMICS -- Finance; Foreign exchange futures; Foreign exchange market; Foreign exchange market; Foreign exchange futures; Electronic books; Electronic books